2016
DOI: 10.1016/j.afjem.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Availability of resources for emergency care at a second-level hospital in Ghana: A mixed methods assessment

Abstract: IntroductionEmergency care is an essential component of health systems, particularly in low- and middle-income countries. We sought to assess the availability of resources to provide emergency care at a second-level hospital in Ghana. By doing so, deficits that could guide development of targeted intervention strategies to improve emergency care could be identified.MethodsA qualitative and quantitative assessment of capacity for care of emergency patients was performed at the Emergency Centre of the Police Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 29 publications
4
53
0
Order By: Relevance
“…Emergency nursing as a profession is very new to Africa and therefore the availability of guidelines and standards is also limited [17]. Improvements in training such as developing an education curriculum for staff in all areas of the emergency care, holding in-service training on protocols for triage, and emergency care could improve nursing care in ED [18]. There should be enough protocols to help nurses deal with emergency cases in EDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency nursing as a profession is very new to Africa and therefore the availability of guidelines and standards is also limited [17]. Improvements in training such as developing an education curriculum for staff in all areas of the emergency care, holding in-service training on protocols for triage, and emergency care could improve nursing care in ED [18]. There should be enough protocols to help nurses deal with emergency cases in EDs.…”
Section: Discussionmentioning
confidence: 99%
“…Existing emergency care systems in Ghana are rudimentary in comparison to those in developed countries [12]. An assessment of an ED at Police Hospital, a second-level hospital in Accra, Ghana, revealed marked deficiencies in many essential items and services [18]. Nurses in Ghana are currently an underdeveloped resource for the provision of high quality emergency care [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lack of clinical protocols in most of the hospitals added another perplexity in trauma management of the injured patients. Implementation of the standardized protocol for trauma care in most of the LMIC's is an area of concern [43][44][45][46] . Moreover, the equipment to manage resuscitation followed by the lack of physical resources such as imaging technologies are some of the barriers to providing effective trauma care.…”
Section: Discussionmentioning
confidence: 99%
“…Using mixed methods, Japiong et al reported from Ghana concerning marked deficiencies in many essential items and services such as basic airway supplies, chest tubes, and several emergency medications. Similarly, substantial deficiencies in capacity were demonstrated across a range of indicators and predominantly affecting publicly funded facilities in Sierra Leone .…”
Section: Introductionmentioning
confidence: 99%